Interaction between BiP and Sec63p is required for the completion of protein translocation into the ER of Saccharomyces cerevisiae (The Rockefeller University Press, 1995)
To clarify the roles of Kar2p (BiP) and Sec63p in translocation across the ER membrane in Saccharomyces cerevisiae, we have utilized mutant alleles of the essential genes that encode these proteins: kar2-203 and sec63-1. Sanders et al. (Sanders, S. L., K. M. Whitfield, J. P. Vogel, M. D. Rose, and R. W. Schekman. 1992. Cell. 69:353-365) showed that the translocation defect of the kar2-203 mutant lies in the inability of the precursor protein to complete its transit across the membrane, suggesting that the lumenal hsp70 homologue Kar2p (BiP) binds the transiting polypeptide in order to facilitate its passage through the pore. We now show that mutation of a conserved residue (A181-->T) (Nelson, M. K., T. Kurihara, and P. Silver. 1993. Genetics. 134:159- 173) in the lumenal DnaJ box of Sec63p (sec63-1) results in an in vitro phenotype that mimics the precursor stalling defect of kar2-203. We demonstrate by several criteria that this phenotype results specifically from a defect in the lumenal interaction between Sec63p and BiP: Neither a sec62-1 mutant nor a mutation in the cytosolically exposed domain of Sec63p causes precursor stalling, and interaction of the sec63-1 mutant with the membranebound components of the translocation apparatus is unimpaired. Additionally, dominant KAR2 suppressors of sec63-1 partially relieve the stalling defect. Thus, proper interaction between BiP and Sec63p is necessary to allow the precursor polypeptide to complete its transit across the membrane.